Short Stay Management of Acute Heart Failure - Peacock, W. Frank; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2012)
This timely book is a road map for defining the care of acute heart failure patients in the short stay or observation unit setting. Produced in collaboration with the Society of Chest Pain Centers, this book provides an understanding of the diverse medical needs and solutions, administrative processes, and regulatory issues necessary for successful management. In an environment of increasing financial consciousness, medical practice is changing drastically. Short stay care is premier among the new specialties that cater to the complex balance of optimizing patient outcomes while minimizing fiscal burdens. The observation unit has proven to be an excellent arena for the care of acute heart failure, replete with opportunities to improve both medical management and quality metrics. Unique to the field, Short Stay Management of Acute Heart Failure, Second Edition is the only book of its kind, providing the medical, regulatory, and economic tools necessary to create and implement successful short stay management protocols and units for the care of the heart failure patient. It is an essential guide for health care professionals and for hospitals and institutions wishing to be recognized as quality heart failure centers as accredited by the Society of Chest Pain Centers.
Society of Chest Pain Centers$1 (BHeart Failure Accreditation -- The Economics and Reimbursement of Congestive Heart Failure -- Regulatory Requirements in Acute Heart Failure -- Quality and Operational Metrics in Heart Failure -- Interaction of Performance Measurements, Staffing, and Facility Requirements for the Heart Failure Observation Unit -- Heart Failure: Epidemiology and Demographics -- Pathophysiology of Acute Decompensated Heart Failure -- The Out-of-Hospital Management of Acute Heart Failure -- Dyspnea Assessment and Airway Management in Acute Heart Failure Syndromes Patients -- Volume Assessment in the Emergency Department -- Diagnostic and Prognostic Biomarkers in Emergency Department Heart Failure -- Emergency Department Therapy of Acute Heart Failure -- Observation Unit Entry Tx and Dispo -- Observation Unit Admission Inclusion and Exclusion Criteria -- Acute Heart Failure in Observation Unit Treatment Protocols -- Education Elements in the Observation Unit for Heart Failure Patients -- Emergency Department and Observation Unit Discharge Criteria -- Effective Discharge Planning -- Outpatient Medication Titration in Acute Heart Failure -- Drugs to Avoid in Acute Heart Failure: Contraindictated Medications and Interactions -- Implications of Atrial Fibrillation in Heart Failure Management -- Implantable Cardiac Devices in the Short Stay Management of Decompensated Heart Failure -- Heart Failure and Kidney Disease: Management in the Short Stay Unit -- Heart Failure Research in the Emergency Department and Observation Unit -- Appendix: Clinical Pathways, Algorithms, Patient Education Tools, and Discharge Instructions.s
Keywords: Medicine; Emergency medicine; Internal medicine; Cardiology; Medicine & Public Health; Cardiology; Emergency Medicine; Internal Medicine